2020
DOI: 10.1007/978-3-030-47717-2_5
|View full text |Cite
|
Sign up to set email alerts
|

On Partitioning of an SHM Problem and Parallels with Transfer Learning

Abstract: In the current work, a problem-splitting approach and a scheme motivated by transfer learning is applied to a structural health monitoring problem. The specific problem in this case is that of localising damage on an aircraft wing. The original experiment is described, together with the initial approach, in which a neural network was trained to localise damage. The results were not ideal, partly because of a scarcity of training data, and partly because of the difficulty in resolving two of the damage cases. I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…The Gnat dataset has been well-studied [40,41,[44][45][46][47], and is an experimental dataset in which an aircraft wing was excited with a band-limited Gaussian noise and the response measured at several locations via uni-axial accelerometers. Inspection panels were subsequently removed, giving pseudo-damage scenarios.…”
Section: Multi-class Case Studymentioning
confidence: 99%
“…The Gnat dataset has been well-studied [40,41,[44][45][46][47], and is an experimental dataset in which an aircraft wing was excited with a band-limited Gaussian noise and the response measured at several locations via uni-axial accelerometers. Inspection panels were subsequently removed, giving pseudo-damage scenarios.…”
Section: Multi-class Case Studymentioning
confidence: 99%
“…In previous work, it was identified that the smaller panels caused confusion during localisation [26]. Furthermore, recent analysis on the dataset has demonstrated that a hierarchy of classifiers can be used to classify whether the class belongs to the large or small panel subsets, before localisation to each specific panel, with the approach showing boosted classification performance when compared to the complete problem [27]. For these reasons this paper considers the localisation problem considering only the large panels, i.e.…”
Section: Overcoming the Repair Problem On The Gnat Aircraft Wingmentioning
confidence: 99%
“…The Gnat aircraft dataset is an experimental dataset that has been well-studied within the field of SHM [36,37,38,39,40,41]. Although the dataset is from one structure, namely an aircraft wing from a Gnat trainer aircraft [37,38], the dataset does form two distinct data domains due to data shift that occurs from changes caused by reattaching inspection panels (even when the torque of the fasteners is monitored [38]).…”
Section: Gnat Aircraft Datasetmentioning
confidence: 99%